Nutrition in the Philippines: The Past for Its Template, Red for Its Color (Cecilia Florencio) - Cabilo, Zuraida Mae D. (Kasarinlan: Philippine Journal of Third World Studies; Vol 19 No 1 (2004): Human Security in Conflict Situations, 2007)
Review of Nutrition in the Philippines: The Past for Its Template, Red for Its Color by Cecilia Florencio.
Keywords: Nutrition